2009
DOI: 10.1158/1055-9965.epi-09-0152
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and Haplotypes in the Caspase-3, Caspase-7, and Caspase-8 Genes and Risk for Endometrial Cancer: A Population-Based, Case-Control Study in a Chinese Population

Abstract: Caspase-3, caspase-7, and caspase-8 are important caspases in the apoptosis pathway and play an important role in the development and progression of cancer. We examined the association between genetic variants in the caspase-3, caspase-7, and caspase-8 genes and risk for endometrial cancer among Chinese women. Genotypes for 1,028 women with endometrial cancer and 1,003 healthy controls were determined with the Affymetrix MegAllele Targeted Genotyping System and Molecular Inversion Probe method. Of 35 selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
5
19
0
Order By: Relevance
“…A previous report has shown an inactivation mutation of CASP7 in esophageal cancer cells (34). Polymorphisms in CASP7 have been examined in several human cancers (35,36) but not in esophageal cancer until our recent report (11). In this study, we identified a significant interaction between CASP7 rs7907519 and smoking in EA cases.…”
Section: Discussionsupporting
confidence: 49%
“…A previous report has shown an inactivation mutation of CASP7 in esophageal cancer cells (34). Polymorphisms in CASP7 have been examined in several human cancers (35,36) but not in esophageal cancer until our recent report (11). In this study, we identified a significant interaction between CASP7 rs7907519 and smoking in EA cases.…”
Section: Discussionsupporting
confidence: 49%
“…Finally, a study of 1028 endometrial cancer patients and 1003 healthy controls examined potential links between caspase-3, -7, and -8 variant alleles and risk of endometrial cancer. Compared with the CC genotype, the GG genotype of rs2705901 in CASP3 was significantly associated with increased cancer risk (Xu et al 2009). Taken together, these results suggest that CASP3 polymorphisms and their haplotypes help to define an individual's genetic susceptibility to cancer development.…”
Section: Caspase-3mentioning
confidence: 99%
“…151 Although somatic CASP3 mutations are rare in most tumors, 152 CASP3-variant alleles have been detected in squamous cell carcinomas of the head and neck (SCCHN) and associated with increased risk of SCCHN. 153 In addition, CASP3-variant alleles are associated with risk of endometrial cancer 154 and NHL 155 and multiple myeloma. 156 CASP3 polymorphisms in some lung cancer patients also show significantly decreased risk of disease.…”
Section: Caspases In Tumorigenesismentioning
confidence: 99%